Replacement names for two species of Noctuidae (Lepidoptera) - Han, H. L.; Kononenko, V. S. (Zootaxa, 2012)
In the course of research on the Eustrotiinae (Noctuidae) we have determined that the African species Eustrotia bella Bethune-Baker, 1911 (nomenclature according to Poole 1989) is congeneric with Maliattha separata Walker, 1863, the type-species of Maliattha Walker, 1863. Characters of Maliattha shared with bella Bethune-Baker are the small size, structure of the palpi and characteristic wing pattern, and male genitalic features including a short uncus, lacking a harpe, a long ribbon-like transtilla, and the presence of a clavus and small sclerotised claws on the tip of the valva (Figs. 1–6). With this generic transfer, the name bella Bethune-Baker, 1911 becomes a secondary junior homonym of Maliattha bella (Staudinger, 1892) and requires a replacement name, which we provide here as Maliattha bethunebakeri, nom. n.